Study on the pathway of energy transition in Inner Mongolia under the “dual carbon” goal - Wei Duan; Wendi Zhao; Desheng Xu (Heliyon)
As an important strategic energy base in China, Inner Mongolia's energy exports are dominated by coal and electricity. Under the background of “double carbon” target, the energy transition of Inner Mongolia is of great significance to China's energy security and carbon emission reduction. Based on the energy policy simulation model (EPS model), this paper explores the path of energy transition in Inner Mongolia by constructing the scenarios of developing renewable energy, developing CCS technology and carbon pricing, and simulating the policy situation based on the reality of Inner Mongolia and the energy transition experience of developed countries and regions. The results show that (1) The energy production and power generation under the development of renewable energy scenario (RE) and carbon pricing scenario (CP) are lower than the “Business as usual” scenario (BAU) for a certain period of time, which affects China's energy security. However, by 2060, power generation and energy production under both scenarios exceed the BAU scenario, and the energy production structure is dominated by renewable energy in both cases. (2) If the Inner Mongolia government focuses on short-term carbon emission reduction, the government should actively promote the establishment of a carbon emission trading market and increase the use of renewable energy through the improvement of the carbon pricing mechanism to promote carbon emission reduction in Inner Mongolia. If the Inner Mongolia government focuses on long-term energy supply stability, it should vigorously develop CCS technology.